Analisis reaksi pasar saham terhadap peristiwa pandemi covid 19 di Indonesia tahun 2021 (Studi pada perusahaan indeks sektor pertambangan Bursa Efek Indonesia) - Noor, M. Fajerian; Lumanauw, Meiske Kristin (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This research aims to examine the stock market reaction to information about the second spike in COVID-19 cases, especially stock prices and trading volume. The research uses an event study approach. The research sample is mining sector index issuers on the Indonesia Stock Exchange in 2021. Historical data uses stock price and trading volume data from 90 days before (T-90) the peak of the second spike in COVID-19 in Indonesia until 90 days after the peak (T+ 90). Based on the analysis, the results obtained: (1) there is no significant difference in abnormal returns between the periods before and after the 2nd peak of COVID-19 in Indonesia (2) there is no significant difference in security return variability between the periods before and after the 2nd spike peak COVID-19 in Indonesia, and (3) there were no significant differences in the mining sector index shares in phase 2 of the peak of COVID-19 cases in Indonesia.